Orbital and millennial Antarctic climate variability over the past 800,000 years - Jouzel J.; Masson Delmotte V.; Cattani O.; Dreyfus G.; Falourd S.; Hoffmann G.; Minster B.; Nouet J.; Barnola J. M.; Chappellaz J.; Fisher H.; Gallet J. C.; et al. (Science, 2007)
A high-resolution deuterium profile is now available along the entire European Project for Ice Coring in Antarctica Dome C ice core, extending this climate record back to marine isotope stage 20.2, ~800,000 years ago. Experiments performed with an atmospheric general circulation model including water isotopes support its temperature interpretation. We assessed the general correspondence between Dansgaard-Oeschger events and their smoothed Antarctic counterparts for this Dome C record, which reveals the presence of such features with similar amplitudes during previous glacial periods. We suggest that the interplay between obliquity and precession accounts for the variable intensity of interglacial periods in ice core records. Northern and Southern hemisphere, methane, ice cores, Greenland, Antarctica, EPICA, Dansgaard–Oeschger events, Atlantic meridional overturning circulation.